1994
DOI: 10.1111/j.1651-2227.1994.tb13237.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the elimination of endotoxin and cytokines with continuous lavage an alternative procedure in necrotizing enterocolitis?

Abstract: HG. Is the elimination of endotoxin and cytokines with continuous lavage an alternative procedure in necrotizing enterocolitis? Acta Padiatr 1994;(suppl 396):24-6. Stockholm. ISSN 0803-5326Ascites fluid was obtained intraoperatively in 12 consecutively treated neonates (6M, 6F, mean weight 940 g, mean gestational age 27th week, lethality 3/12) suffering from necrotizing enterocolitis (NEC). The concentrations of endotoxin and cytokines (IL-1, IL-6, TNF) were determined. Endotoxin and interleukins were excessiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The available clinical and animal studies suggest that the major etiologic factors include (1) intestinal mucosal injury, (2) presence of bacteria, (3) presence of bacterial substrate (e.g., feedings), and (4) immunologic immaturity of the preterm intestinal tract [3, 8, 10, 111. The histologic findings of coagulation necrosis, acute and chronic inflammation, ulceration, and hemorrhage are pathologic hallmarks of the disease [ 121. Several inflammatory cytokines that mediate inflammatory cell recruitment and activation and amplify the immune response in local host defense [ 13-1 51 have been implicated in NEC, including tumor necrosis-factor-a (TNF-a), interleukin-6 (IL-6), and IL-1p [16][17][18]. In most of the prior studies, cytokines were measured in plasma [16,171 or ascites fluid [18] rather than in affected intestinal tissue.…”
mentioning
confidence: 99%
“…The available clinical and animal studies suggest that the major etiologic factors include (1) intestinal mucosal injury, (2) presence of bacteria, (3) presence of bacterial substrate (e.g., feedings), and (4) immunologic immaturity of the preterm intestinal tract [3, 8, 10, 111. The histologic findings of coagulation necrosis, acute and chronic inflammation, ulceration, and hemorrhage are pathologic hallmarks of the disease [ 121. Several inflammatory cytokines that mediate inflammatory cell recruitment and activation and amplify the immune response in local host defense [ 13-1 51 have been implicated in NEC, including tumor necrosis-factor-a (TNF-a), interleukin-6 (IL-6), and IL-1p [16][17][18]. In most of the prior studies, cytokines were measured in plasma [16,171 or ascites fluid [18] rather than in affected intestinal tissue.…”
mentioning
confidence: 99%
“…Epidemiological studies showed that prematurity, infection, early enteral feeding, and hypoxia are risk factors for NEC [3,4]. Although the definitive pathogenesis of the disease is not completely understood, a final common pathway of NEC was found to be the endogenous production of mediators and a systemic inflammatory reaction similar to that in sepsis and adult respiratory distress syndrome [4][5][6]. Concentrations of various mediators were found to be increased in plasma of human neonates with NEC [3][4][5][7][8][9][10].…”
Section: Introductionmentioning
confidence: 84%
“…In patients with NEC undergoing surgical intervention, IL-1 concentrations are elevated in peritoneal uid (52). Serum concentrations of IL-1 and IL-1ra are also elevated in more severe cases of NEC, implying that there is an association between NEC and this proinammatory cytokine (53).…”
Section: Interleukin-1mentioning
confidence: 99%